Relationship Between Characteristics Of Supervisory With Tuberculosis’s Patient Compliance In Puskesmas Pragaan 2016 - Nazilatul Fadlilah (Universitas Airlangga, 2017)
The incidence of tuberculosis (TB) in Sumenep District is still a priority health problem, especially in the Pragaan area. The Public Health Center (PHC) of Pragaan is one of the PHC in Sumenep District which has the highest TB incidence rate with success rates in 2015 to 2016 declining. This study aims to describe and analyze the relationship between knowledge, attitudes, and characteristics of the Drug supervisor (PMO) with the compliance of pulmonary TB patients in PHC of Pragaan in Sumenep in 2016. This research is analytic study using the case-control method and analyzed by testing chi-square statistics. The study population was all PMOs from pulmonary TB patients seeking treatment at the PHC of Pragaan from January to December 2016, totaling 106 patients. The sample of this study was 60 people, 20 PMO cases, and 40 PMO controls. This study uses an interview method with questionnaire guidelines. The results of the study found that the incidence of pulmonary tuberculosis in the PHC of Pragaan was 104 patients. The information obtained is presented in tabular and narrative form. The results of the chi-square statistical test found that there was no relationship between sex (p = 0.855), age (p = 0.106), occupation (p = 0.325), last education (p = 0.656), and the closeness relationship between PMO and patients (p = 0.112) with compliance with pulmonary TB patient treatment, however, there is a relationship between knowledge (p = 0.004) and attitude (p = 0.003) with compliance with TB patient treatment. Knowledge and attitude are risk factors related to TB patient compliance.